Identificação das Redes Criminais de Bagé - (:unkn) unknown (Universidade Federal do Pampa, 2016)
With the growth of crime and consequently increase of the number of police reports recorded in the public security agencies a lot of data on criminal actions is being generated at a higher speed than the security analysts can explore. Also, there is a tendency that these criminals act jointly and organized manner in the execution of crimes. Due to this, this paper proposes the use of a technique on Social Network Analysis to enable automated analysis of a large number of incidents recorded in digital security agencies of a city. Using this technique, and based on actual data provided by a public security organ, it was carried out the identification and analysis of criminal social network of the city of Bagé. In addition, it was developed a tool that will continue assisting law enforcement agencies in the identification of criminal networks in the future.
Keywords: Análise de Redes Sociais; segurança pública; rede criminal; Processamento de Linguagem Natural; Gephi; Social Network Analysis; public security; criminal network; Natural Language Processing; CNPQ::ENGENHARIAS